Évolution technique et objectivité technique chez Leroi-Gourhan et Simondon - Xavier Guchet (Appareil)
Does a theory of “technological evolution” prompt the idea that technology is a natural phenomenon? The analogy between natural evolution and technological change has been often outlined in paleoanthropology and in various general theories of machines since the 19th century. Does this analogy mean that technology is embedded in a purely natural and even biological process? Beyond its social and cultural features, technology would be viewed as an output of a biological evolution process, as the “externalization” of biological functions. Against this approach to “technological evolution” as a purely biological vision of technology, we argue that this concept has been shaped in order to delineate an autonomous field of human activity and knowledge, irreducible to biology. The article focuses on French paleontologist A.Leroi-Gourhan’s and French philosopher G.Simondon’s theories of “technological evolution”.